How decisions about fitting species distribution models affect conservation outcomes. Issue 4 (9th February 2021) - Muscatello, Angela; Elith, Jane; Kujala, Heini
Abstract: Species distribution models (SDMs) are increasingly used in conservation and land‐use planning as inputs to describe biodiversity patterns. These models can be built in different ways, and decisions about data preparation, selection of predictor variables, model fitting, and evaluation all alter the resulting predictions. Commonly, the true distribution of species is unknown and independent data to verify which SDM variant to choose are lacking. Such model uncertainty is of concern to planners. We analyzed how 11 routine decisions about model complexity, predictors, bias treatment, and setting thresholds for predicted values altered conservation priority patterns across 25 species. Models were created with MaxEnt and run through Zonation to determine the priority rank of sites. Although all SDM variants performed well (area under the curve >0.7), they produced spatially different predictions for species and different conservation priority solutions. Priorities were most strongly altered by decisions to not address bias or to apply binary thresholds to predicted values; on average 40% and 35%, respectively, of all grid cells received an opposite priority ranking. Forcing high model complexity altered conservation solutions less than forcing simplicity (14% and 24% of cells with opposite rank values, respectively). Use of fewer species records to build models or choosing alternative bias treatments had intermediate effects (25% and 23%, respectively). Depending on modeling choices, priority areas overlapped as little as 10–20% with the baseline solution, affecting top and bottom priorities differently. Our results demonstrate the extent of model‐based uncertainty and quantify the relative impacts of SDM building decisions. When it is uncertain what the best SDM approach and conservation plan is, solving uncertainty or considering alterative options is most important for those decisions that change plans the most. Abstract : Article impact statement : Methodological decisions on how species distribution models (SDMs) are built can alter locations of priority areas up to 90%. Abstract : Efecto de las Decisiones sobre Modelos Adecuados de Distribución de Especies sobre los Resultados de Conservación Resumen: Los modelos de distribución de especies (MDEs) se usan cada vez más en la planeación de la conservación y del uso de suelo como contribuciones para describir los patrones de la biodiversidad. Estos modelos pueden construirse de maneras diferentes y las decisiones sobre la preparación de datos, selección de las variables de pronóstico y la adecuación y evaluación del modelo alteran las predicciones resultantes. Generalmente, la verdadera distribución de las especies se desconoce y se carece de los datos independientes para verificar cuál variante de MDE elegir. Dicha incertidumbre con los modelos es preocupante para los planificadores. Analizamos cómo once decisiones rutinarias sobre el modelo, su complejidad, los predictores, el tratamiento del sesgo y el establecimiento de umbrales para los valores pronosticados alteraron los patrones de prioridades de conservación para 25 especies. Creamos los modelos con MaxEnt y los corrimos en Zonation para determinar el rango de prioridad de los sitios. Aunque todas las variantes de los MDE tuvieron un buen desempeño (área bajo la curva >0.7), todos produjeron predicciones espaciales diferentes para las especies y diferentes soluciones prioritarias de conservación. Las prioridades tuvieron la alteración más fuerte cuando se decidió no considerar el sesgo o aplicar umbrales binarios a los valores pronosticados; en promedio, el 40% y 35%, respectivamente, de todas las celdas de la cuadrícula recibieron una clasificación opuesta de prioridad. Cuando se forzó una complejidad alta para el modelo, se alteraron menos las soluciones de conservación que cuando se forzó la simplicidad (14% y 24% de las celdas con valores opuestos de clasificación, respectivamente). El uso de menos registros de especies para construir modelos o elegir tratamientos alternativos para el sesgo tuvo efectos intermedios (25% y 23%, respectivamente). Según la elección del modelo, las áreas prioritarias se traslaparon mínimamente en 10–20% con la solución de la línea base, afectando a las prioridades de arriba y abajo de maneras diferentes. Nuestros resultados demuestran el alcance de la incertidumbre basada en los modelos y cuantifican el impacto relativo de las decisiones al construir los MDE. Cuando no es seguro cuál es el mejor plan de conservación ni la mejor estrategia de MDE, es de suma importancia solucionar la incertidumbre o considerar soluciones alternativas para aquellas decisiones que más cambian los planes.